Prevalence, awareness, treatment, and control rates of hypertension in patients hospitalized with atrial fibrillation in China: Findings from the CCC-AF project - Sun, Zhaoqing; Hao, Yongchen; Liu, Jun; Yang, Na; Qi, Yue; Hu, Danqing; Yang, Yiqian; Wang, Haimei; Zhao, Dong; Sang, Caihua; Liu, Jing (Frontiers in Cardiovascular Medicine, 2022)
Background: The status of hypertension in patients with atrial fibrillation (AF) remains unknown in China. Methods: This study used data from patients hospitalized with AF recruited by the Improving Care for Cardiovascular Disease in China-AF (CCC-AF) project from 236 hospitals enrolled by geographic-economic level in China from 2015 to 2019. The prevalence, awareness, treatment, and control rates of hypertension in patients hospitalized with AF were estimated. Multivariable logistic regression was used to analyze the factors associated with uncontrolled hypertension. Results: Among 60 390 patients hospitalized with AF, the prevalence of hypertension according to the 2018 Chinese hypertension guidelines was 66.1%. The awareness, treatment, and control rates of hypertension were 80.3%, 55.8%, and 39.9%, respectively. Among patients treated for hypertension, the treatment control rate was 46.2%. These rates varied according to patient clinical characteristics and geographic regions. The young (18-44 and 45-54 years old), rural insurance, alcohol drinking, history of heart failure, valvular AF, first diagnosed AF, and permanent AF, were associated with uncontrolled hypertension. Under the 2017 American College of Cardiology/American Heart Association (ACC/AHA) hypertension guidelines, the prevalence of hypertension was 79.3%, and the control and treatment control rates dropped to 16.7% and 21.2%, respectively. Conclusion: Hypertension is common in patients hospitalized with AF in China. Although most patients were aware of their hypertensive status, the treatment and control rates of hypertension were still low. The management of hypertension in patients with AF needs to be further improved.